Kontribusi Imām Al-Nawāwī Dalam Penulisan Kitab Hadis Pada Abad VII (Studi Kitab Riadlu Al-Shalihin) - Roziqin, Muhammad Khoirur; Muhid, Muhid; Nurita, Andris (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2023)
The history of scientific journeys, especially in the writing of hadith, developed according to the demands of the times, several books of hadith that appeared in each period always brought the author's contribution in each of their respective books until in the VII century Imām al-Nawawi appeared with the book Riyadlu al-Salihin which became a book with the theme fadhail which is much in demand by all people at all times. Several books were found that preceded the writing of Riyadlu al-Shalihin such as the book Targhib Wa Tarhib by al-Mundziri, but in reality the book Riyadlu al-Shalihin is more in demand by various groups of people. After conducting qualitative research with a holistic approach, it was found that the background of Imam al-Nawawi's writing in writing Riyadlu as-Shalihin was based on the demands of the times and the social conditions of society which tended to prioritize worldly interests so that Imam al-Nawawi was moved to collect hadiths in a book to direct people -people of original purpose created, with a very systematic methodology of writing hadith by writing verses of the Koran at the beginning of the chapter and equipped with an explanation for each sentence at the end of the History became the major contribution of Imam al-Nawawi in writing hadith in the VII century so that the book with the theme Fadhail al -A`mal is more acceptable.